Covid-19 And Diagnosis-related Group In One Of The University Hospitals In Malaysia: Patient Classifications And Associated Hospital Costs - Mohd Hafiz Jaafar; Mohamad Helmi Mohamad Yasim; Mohmmad Salleh Yahya; Maznah Dahlui; Nadia Samsudin; Sharifah Faridah Syed; Adeeba Kamarulzam; Nazirah Hasnan; Thinni Nurul Rochmah; Awang Bulgiba; Amirah Azzeri (AME Publishing Company, 2024)
Non-Indexed Publication